2006
DOI: 10.1111/j.1440-1754.2006.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and management of childhood overweight and obesity by clinicians

Abstract: GPs and paediatricians have the opportunity to screen children for overweight and obesity during their everyday practice. Accurate determination of weight status cannot be performed by visualisation alone and all children should have height and weight measured and correctly interpreted. Some areas of current GP and paediatrician management of overweight and obese children fall short of the NHMRC clinical guidelines and areas for improvement are highlighted in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 19 publications
7
65
0
1
Order By: Relevance
“…23 Another Australian study found that most surveyed primary care providers did not routinely measure children' s height or weight or calculate BMI. 24 The LEAP (Live, Eat, and Play) study revealed that only 50% of children were weighed and measured during their visit to a primary care provider' s office. 10,11 The literature provides some insights into potential reasons for that phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another Australian study found that most surveyed primary care providers did not routinely measure children' s height or weight or calculate BMI. 24 The LEAP (Live, Eat, and Play) study revealed that only 50% of children were weighed and measured during their visit to a primary care provider' s office. 10,11 The literature provides some insights into potential reasons for that phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] These problems are apparently attributable to a low utilisation of BMI percentile charts in common practice. 15,17,18,20,21 Poor detection of overweight, however, was not the only barrier to participation in our study, since many more families were informed about their child being overweight than were enrolled for training. Reasons for the low interest of these families may be a lower treatment motivation in families with overweight children (who do not particularly suffer from weight-related complaints), denial of relevance of the condition, or sense of parental guilt, if non-physiological reasons for excess weight are acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Parents need to identify their children's weight problems and understand the accompanying short and long-term risks and they look to their pediatricians for advice and guidance (Hernandez et al, 2010). But parents and pediatricians often underestimate children's body size (Akerman et al, 2007;Chaimovitz et al, 2008;Jones et al, 2011;Lampard et al, 2008;Parry et al, 2008;Perrin et al, 2005;Spurrier et al, 2006;Tschamler et al, 2010;Wald et al, 2007). Unrecognized obesity is especially high for obese parents, for overweight as compared to obese children (Taveras et al, 2011), for lower socioeconomic parents (Rivera-Soto and Rodriguez-Figueroa, 2012) and for Hispanics (Intagliata et al, 2008), African Americans (West et al, 2008) and Native Americans (Arcan et al, 2012) and could impair parental motivation to adopt weight control measures (Vuorela et al, 2010) and to participate in obesity reduction programs (Taveras et al, 2011).…”
Section: Introductionmentioning
confidence: 97%